RUMPUT KEBAR (Biophytum umbraculum Welw): PEMANFAATANNYA DI INDONESIA, FITOKIMIA, DAN BIOAKTIVITAS - Anisatu Z. Wakhidah (Jurnal Pro-Life, 2020)
Besides the very high diversity of flowering plants, Indonesia is also overflowing with beneficial plants. The number of Indonesia plant species that used as medicine is the second-highest of all utilization (21%). Kebar grass (Biophytum umbraculum Welw) is one of plant that has been widely used as medicine by the people of Indonesia. The people of Papua uses kebar grass as a women fertility drug for generations. Kebar grass is also reported as medicine for various other uses such as mouthwash for thrush, an antidote for snakebite poisons, and laxatives. Based on this information, documentation is needed regarding the various uses of kebar grass in Indonesia, the phytochemical content, and bioactivity. This research was conducted in the literature study method. The data obtained were analyzed and then presented in tabular form and explained descriptively. The results of the study showed the use of kebar grass in Indonesia, among others, improving fertility, as fodder to multiply livestock, herbal medicines in the form of simplicia products. Kebar grass contains various phytochemicals such as alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, glycosides, vitamin E, vitamin A, 17 amino acids; isoflavones, iron, calcium, and phosphorus. Meanwhile, the bioactivity of chemical compounds contained is antioxidants, anticancer, antifungal, anthelmintic, testosterone activity, estrogenic activity, larvicidal effects, and anticholesterol. With the content of phytochemical compounds and bioactivity, kebar grass can be used as a herbal medicine in overcoming fertility problems and has the potential to be developed as a medicine for intestinal worms, cancer, and diseases related to cholesterol. Keywords: bioaktivitas, fitokimia, pemanfaatan, reproduksi, Rumput Kebar